ICE specification for piling and embedded retaining walls (Thomas Telford, 2007)
This edition is designed to be used as the new technical specification for piling & embedded walling works either on land or near to the shore. It documents the latest piling techniques & procurement methods used in the foundations sector whilst incorporating the changes introduced by the new European Standards.
Previous ed. published as: Specification for piling and embedded retaining walls. 1996.
Keywords: Retaining walls -- Specifications -- Great Britain.; Piling (Civil engineering) -- Specifications -- Great Britain.; Great Britain.; elektronické knihy; electronic books